2011
DOI: 10.5539/ass.v7n4p36
|View full text |Cite
|
Sign up to set email alerts
|

“No one can whistle a symphony. It takes an orchestra to play it.” H. E. Luccock

Abstract: An innovative teamwork training module was developed for business students as part of an Australian Learning and Teaching Council (ALTC) grant supporting the acquisition of generic skills. The module content was based on teamwork theory and research and was delivered in a one-off training session using action learning pedagogy that promoted team development and experiential learning. Initial student feedback indicates that this model of teamwork training has broader applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Many articles (e.g. Gilson, Maynard & Bergiel, 2013;Kirby, 2011;Snyder, 2010) reported that for some educators it is not always clear how they should teach teamwork skills; therefore, educators may be inadequately prepared to take on the task (Tombaugh & Mayfi eld, 2014). Th is has an impact on both educators and students.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles (e.g. Gilson, Maynard & Bergiel, 2013;Kirby, 2011;Snyder, 2010) reported that for some educators it is not always clear how they should teach teamwork skills; therefore, educators may be inadequately prepared to take on the task (Tombaugh & Mayfi eld, 2014). Th is has an impact on both educators and students.…”
Section: Discussionmentioning
confidence: 99%
“…The process of teamwork was discussed in 10 (17.5%) journal articles. Three articles (Kirby, 2011; Pineda & Lerner, 2006; Rapp & Mathieu, 2007) specifically explained and grouped team processes into three main processes: transition, action, and interpersonal. Kirby (2011) related team formation to the transition process, Pineda and Lerner (2006) discussed team goals as a team transition process related to planning, while Rapp and Mathieu (2007) focused on the establishment of team member roles and responsibilities and team charters.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the articles (e.g., Gilson et al, 2013; Kirby, 2011; McCorkle et al, 1999; Snyder, 2010) reported that for some educators it is not always clear how they should teach teamwork skills, and therefore, educators may be inadequately prepared (Tombaugh & Mayfield, 2014) to take on the task. This has an impact on both educators and students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations